2014
DOI: 10.1073/pnas.1405083111
|View full text |Cite
|
Sign up to set email alerts
|

Methylation protects microRNAs from an AGO1-associated activity that uridylates 5′ RNA fragments generated by AGO1 cleavage

Abstract: In plants, methylation catalyzed by HEN1 (small RNA methyl transferase) prevents microRNAs (miRNAs) from degradation triggered by uridylation. How methylation antagonizes uridylation of miRNAs in vivo is not well understood. In addition, 5′ RNA fragments (5′ fragments) produced by miRNA-mediated RNA cleavage can be uridylated in plants and animals. However, the biological significance of this modification is unknown, and enzymes uridylating 5′ fragments remain to be identified. Here, we report that in Arabidop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 43 publications
(60 reference statements)
7
124
0
Order By: Relevance
“…This is consistent with trimming of the 39-overhang of the AGO1-bound guide strand in an siRNA duplex. AGO1-dependent 39-modifications, including trimming and uridylation, have previously been observed (Zhai et al, 2013;Ren et al, 2014), and it is possible that the trimming observed here is a manifestation of the same phenomenon that produces the previously described AGO1-dependent 39-trimming of small RNA. We could not clearly assign the faster migrating species of siRNAs other than siR255 to reads detected by deep sequencing.…”
Section: The Shorter Sir255 Species Arises By 39-trimmingsupporting
confidence: 71%
“…This is consistent with trimming of the 39-overhang of the AGO1-bound guide strand in an siRNA duplex. AGO1-dependent 39-modifications, including trimming and uridylation, have previously been observed (Zhai et al, 2013;Ren et al, 2014), and it is possible that the trimming observed here is a manifestation of the same phenomenon that produces the previously described AGO1-dependent 39-trimming of small RNA. We could not clearly assign the faster migrating species of siRNAs other than siR255 to reads detected by deep sequencing.…”
Section: The Shorter Sir255 Species Arises By 39-trimmingsupporting
confidence: 71%
“…In Arabidopsis, the RISC 39-cleaved fragment contains a free 59-monophosphate, making it a substrate for XRN4 (Souret et al, 2004). RISC 59-cleaved fragments undergo rapid turnover upon uridylation at their 39 end by the miRNA nucleotidyl transferase HEN1 SUPPRESSOR1 (Ren et al, 2014). The pathways participating in RISC 59-cleaved fragment demise could include 59-39 decay by XRN4 (Ren et al, 2014), although the mechanism of the prerequisite removal of the 59 cap from these fragments is largely unknown.…”
Section: Xrn4-mediated Cotranslational Decaymentioning
confidence: 99%
“…RISC 59-cleaved fragments undergo rapid turnover upon uridylation at their 39 end by the miRNA nucleotidyl transferase HEN1 SUPPRESSOR1 (Ren et al, 2014). The pathways participating in RISC 59-cleaved fragment demise could include 59-39 decay by XRN4 (Ren et al, 2014), although the mechanism of the prerequisite removal of the 59 cap from these fragments is largely unknown. Alternatively, the uridylated fragments may be degraded in the 39 to 59 direction by the exosome (see below).…”
Section: Xrn4-mediated Cotranslational Decaymentioning
confidence: 99%
“…40 In a recent study, we show that HESO1 is responsible for the uridylation of 5 0 CPs in Arabidopsis. 41 A reduction in uridylation in heso1-2 increases the accumulation of 5 0 CP, demonstrating that uridylation triggers degradation of 5 0 CP. 41 The proportion of 3 'truncated 5 0 CPs is increased by heso1 relative to wild-type plants (WT), suggesting that uridylation may cause 5 0 CP degradation through a mechanism different from 3 0 -to-5 0 trimming.…”
Section: Papd4/gld-2 Mediatedmentioning
confidence: 92%